A Closely-Held Companies Act for New Zealand - Farrington, Matthew (Victoria University of Wellington Law Review, 2007)
This paper examines the law relating to closely-held companies. It concludes that the Companies Act's regulatory requirements imposed on directors to ensure accountability to shareholders do not have any benefit where companies are closely-held. The costs arising from such regulatory requirements are therefore unjustified. The paper therefore argues that New Zealand should adopt a new flexible and accessible statute designed to meet the needs of closely-held companies. This statute should be in addition to the existing Companies Act, and should be informed by comparative precedent. This paper argues that the key features of this statute should include removing the distinction between shareholders and directors. This in turn removes the need to impose regulatory requirements on directors in favour of shareholders. The other features relating to defining a closely-held company, limited liability, protections for creditors, and relations between "principals" are also considered in this paper. The net result is a simple, straightforward set of requirements suitable for closely-held companies in New Zealand, without onerous or unjustified compliance requirements.